La profecía de Apolo en El rapto de Helena de Draconcio (Romul. 8) - Marrón, Gabriela Andrea (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2017)
In the first part of this article we will analyze the discussion established by Dracontius through the appropriation and reinsertion of certain Virgilian an Statian syntagmas, orientated to show the fallacious and treacherous nature of Apollo’s prophecy in the De raptu Helenae. In the second part, we will demonstrate that the negative characterization of this divinity in the poem is projected, in turn, towards the textual universe of the Aeneid, proposing a reading inscribed in the same exegetical line developed in Africa, a century before, by Augustine of Hippo.